Sex Differences in the Association Between Lipoprotein(a) and Cardiovascular Outcomes: The MGB Lp(a) Registry - Gurleen Kaur; Adam N. Berman; David W. Biery; Stephanie A. Besser; Wanda Y. Wu; Brittany Weber; Michael C. Honigberg; Khurram Nasir; Martha Gulati; Marcelo F. Di Carli; Leslee J. Shaw; Deepak L. Bhatt; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Sex‐based differences in the association of lipoprotein(a) with cardiovascular outcomes have not been well established for those without prior atherosclerotic cardiovascular disease. Methods and Results Patients with no baseline atherosclerotic cardiovascular disease were identified in the MGB (Mass General Brigham) Lp(a) Registry, a retrospective cohort of patients who had lipoprotein(a) measured from 2000 to 2019. Lipoprotein(a) percentile groups were categorized as 1st to 50th (reference), 51st to 70th, 71st to 90th, and 91st to 100th. The primary outcome was a composite of fatal or nonfatal myocardial infarction, or fatal or nonfatal ischemic stroke. Cox proportional hazard modeling was used to assess the association of lipoprotein(a) with the primary outcome. Among 6238 patients with no baseline atherosclerotic cardiovascular disease, 45% were women. Women had higher total cholesterol, low‐density lipoprotein cholesterol, and median lipoprotein(a) (33.2 versus 28.9 nmol/L; P<0.001), whereas men had higher rates of diabetes and atrial fibrillation. Higher lipoprotein(a) was associated with an increased incidence of the primary composite outcome, with patients in the 91st to 100th percentile group (≥216 nmol/L) having an adjusted hazard ratio (HR) of 2.07 (95% CI, 1.31–3.25; P<0.01) in women and 2.39 (95% CI, 1.57–3.65; P<0.01) in men, with no interaction based on sex. When examining individual outcomes, the strongest association was present between lipoprotein(a) and fatal or nonfatal myocardial infarction (women: adjusted HR, 2.61 [95% CI, 1.48–4.61]; men: adjusted HR, 3.36 [95% CI, 2.01–5.60]). When stratifying by age, female sex was associated with a lower risk of fatal or nonfatal myocardial infarction in those aged <60 years; however, among older individuals, the risk conferred by elevated lipoprotein(a) was similar between men and women. Conclusions Among individuals with no prior atherosclerotic cardiovascular disease, elevated lipoprotein(a) is associated with higher rates of cardiovascular outcomes, particularly myocardial infarction, in both women and men.